KONSERVASI KUPU-KUPU SEBAGAI SERANGGA PENYERBUK YANG PENTING DI TAMAN NASIONAL BANTIMURUNG-BULUSARAUNG - Sri Nur Aminah Ngatimin (Jurnal Penelitian Kehutanan BONITA, 2019)
The purpose of study is to identify the species and frequency of butterfly visited on three types of flowers namely: Ixora paludosa, Hibiscus rosa-chinensis and Clerodendron japonicum. The information is very useful in the conservation effort of pollinator insects, especially butterflies that live around the Bantimurung-Bulusaraung National Park, Maros district, South Sulawesi, Indonesia.  Research activities in the field trials were located in Simbang village (5 ° 01'23.2 "S and 119 ° 40'33.6" E), Maros district, South Sulawesi. The research was conducted in August to September 2018. There were two families butterflies visited the flowers i.e : Pieridae and Papilionidae. Six species of butterflies visited I. paludosa flowers, four species visited H. rosa chinensis  and seven species visited C. japonicum. The dominant butterfly species visited I. paludosa : Graphium agamemnon and Catopsilia scylla. The species of butterflies in H. rosa-chinensis are Papilio demolion and Troides helena, while those who frequently visited C. japonicum flower: C. pomona and C. scyllaKey words : butterfly, nectar, insect pollinator, Bantimurung, Sulawesi